STUDI KASUS ANALISA KERUSAKAN ABUDMENT JEMBATAN SEI. BAHALANG KALIMANTAN TENGAH - Gawit Hidayat (INFO-TEKNIK, 2010)
Bahalang bridge is a truss bridge B Class across Bahalang river in Ampah (Central Kalimantan), was built as conneting road for transport coal. The bridge building has a problem. It’s like an abutment failure in eastern abutment of Bahalang bridge. This abutment rotate 30 degree, so, the back side of abutmen has decline about 2 metres and slipped from its place to the river about 1 metre.The purposes of this study are to analyze of soil layer behavior and to find out main cause of damage on the abutment. Writer used approach calculation analysis of collapse using Plaxis and Xstabl.There is two options of calculate. Option one high of  water level river are in place (29,5 metres). In Xstabl show SFmin= 0,764 and Plaxis show total displacements=  64,5 metres. In option two where is high of water level  river assumsed (27,4 meters). In Xsstabl show SFmin= 0,807 and Plaxis show total displacements= 4,15 metres. From several alternatives conditions wich was analyzed by Plaxis, the collapse is known happened  during the placement of the fill in the eastern approach. Fill comprised sand material that was being placed rapidly by direct dumping from trucks and spreading by excavator. The results are total displacement= 6,45 metres. Pile bending moment result over the bending moment allowable value. That is 57,81 kNm on front pile, and 63,90 kNm on back pile. Abudment damage can be concluded due to the displacement of excess, so it is potentially broken pile